Impact of Maleic Anhydride, Nanoclay, and Silica on Jute Fiber-reinforced Polyethylene Biocomposites - Md Rezaur, Rahman; Md Mizanur, Rahman (www.ncsu.edu, 2016)
Jute fiber/polyethylene biocomposites were prepared using a hot press molding technique. The effects of maleic anhydride, clay, and silica on the physical, mechanical, and thermal properties of jute fiber-reinforced polyethylene (PE) biocomposites with different fiber loadings (5, 10, 15, and 20 wt.%) were investigated. The biocomposites were characterized by Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and thermogravimetric analysis (TGA). The mechanical properties were determined using a universal testing machine. The biocomposite specific surface area, pore volume, and pore size were investigated using the Brunauer-Emmett-Teller (BET) equation. Because of the Si-O-Si stretching vibration, the peak representing the O-H group significantly decreased in the range of 3200 to 3600 cm−1. Jute fiber/PE Maleic anhydride silica composite (JFPEMASC) showed smoother surfaces, which indicated good distribution and better interfacial bonding between the fibers and matrix. The jute fiber/polyethylene/silica composites had a higher surface area and pore volume, with a lower pore size. JFPEMASC was more thermally stable than the other composites, with higher activation energy. JFPEMASC had the highest Young’s modulus among all the biocomposites.